2020
DOI: 10.3390/en13184963
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Auction for P2P Renewable Energy Trading with Dynamic Energy Storage Management

Abstract: In this paper, a peer-to-peer (P2P) renewable energy trading mechanism for microgrids when energy suppliers are equipped with storage devices is studied. A dynamic energy storage management strategy based on the local trading price is proposed and each supplier decides the amount of energy to be sold and stored in real time. An iterative auction algorithm is presented to obtain the market equilibrium and optimal energy allocation schedule. The economic analysis of introducing energy storage devices in this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…At the same time, P2P power generation is traded across the energy industry and is now evolving. The authors suggested in [91] that P2P assists individual consumers to become consumers and exchange surplus resources with competitors. The use of on-site PV characterizes Self-consumption.…”
Section: Energy Domain Prosumer Classificationsmentioning
confidence: 99%
“…At the same time, P2P power generation is traded across the energy industry and is now evolving. The authors suggested in [91] that P2P assists individual consumers to become consumers and exchange surplus resources with competitors. The use of on-site PV characterizes Self-consumption.…”
Section: Energy Domain Prosumer Classificationsmentioning
confidence: 99%
“…Since the blockchain is unchangeable and distributed, this architecture guarantees that all transactions are accessible to customers, big energy providers and governments. Government supervision of the energy-sharing industry requires a forum [ 90 ]. All parties will have increased vigor and prospects.…”
Section: Peer-to-peer Energy Tradingmentioning
confidence: 99%
“…As an electricity service provider of the P2P trading market, the retailer will facilitate the electricity trading by determining whether the total electricity bid by all sellers are enough to meet the demands of all buyers at the market clearing price and advising the participants to rebid if necessary. Further, the retailer will also establish an appropriate market clearing price, for example, double auction ( Chen et al., 2019 ), mid-market rule ( Alam et al., 2019 ), modified auction ( Zhang et al., 2020a ), or game theory ( Paudel et al., 2019 ), to facilitate the flow of electricity from sellers to buyers. If needed, the retailer will also fulfil the electricity demand of the selected buyers, if needed, through the traditional retailer-based market mechanism.…”
Section: P2p Market With Retailermentioning
confidence: 99%